The Interaction between Candida krusei and Murine Macrophages Results in Multiple Outcomes, Including Intracellular Survival and Escape from Killing - García-Rodas, Rocío (American Society for Microbiology, 2011)

(untitled)
Candida krusei is a fungal pathogen of interest for the scientific community for its intrinsic resistance to fluconazole. Little is known about the interaction of this yeast with host immune cells. In this work, we have characterized the outcome of the interaction between C. krusei and murine macrophages. Once C. krusei was internalized, we observed different phenomena. In a macrophage-like cell line, C. krusei survived in a significant number of macrophages and induced filamentation and macrophage explosion. Phagocytosis of C. krusei led to actin polymerization around the yeast cells at the site of entry. Fluorescent specific staining with anti-Lamp1 and LysoTracker indicated that after fungal internalization, there was a phagolysosome maturation defect, a phenomenon that was more efficient when the macrophages phagocytosed killed yeast cells. Using cell line macrophages, we also observed macrophage fusion after cell division. When we used primary resident peritoneal macrophages in addition to macrophage explosion, we also observed a strong chemotaxis of uninfected macrophages to regions where C. krusei-infected macrophages were present. We also noticed yeast transfer phenomena between infected macrophages. Primary macrophages inhibited pseudohypha elongation more efficiently than the macrophage-like cell line, suggesting that C. krusei infection was better controlled by the former macrophages. Primary macrophages induced more tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) than the macrophage-like cell line. Our results demonstrate that C. krusei can exploit the macrophages for replication, although other different outcomes are also possible, indicating that the interaction of this pathogen with phagocytic cells is very complex and regulated by multiple factors.